Technique and outcome of domino liver transplantation from patients with maple syrup urine disease: Expanding the donor pool for live donor liver transplantation. Issue 11 (6th October 2019) - Celik, Neslihan; Kelly, Beau; Soltys, Kyle; Squires, James E.; Vockley, Jerry; Shellmer, Diana A.; Strauss, Kevin; McKiernan, Patrick; Ganoza, Armando; Sindhi, Rakesh; Bond, Geoffrey; Mazariegos, George; et al.
Abstract: Aim/Background: Domino liver transplantation (DLT) using liver allografts from patients with metabolic disorders enhances organ utilization. Short‐ and long‐term course and outcome of these patients can impact the decision to offer this procedure to patients, especially those with diseases that can potentially be cured with liver transplant. We reviewed the outcomes of DLT from maple syrup urine disease (MSUD) patients in our large academic pediatric and adult transplant program. Methods: All patients receiving DLT were analyzed retrospectively with a minimum of one‐year follow‐up period for patient and donor characteristics, early and late postoperative complications and patient and graft survival with their MSUD donors in terms of age, weight, MELD/PELD scores, cold ischemia time, postoperative leucine levels, and peak ALT (alanine aminotransferase) levels during the first 48 postoperative hours. Results: Between 2006 and May 2019, 21 patients underwent domino liver transplantation with live donor allografts from MSUD patients. Four patients transplanted for different metabolic diseases are focus of a separate report. Seventeen patients with minimum one‐year follow‐up period are reported herein. The indications were primary sclerosing cholangitis (PSC, n = 4), congenital hepatic fibrosis (CHF, n = 2), alpha‐1 antitrypsin deficiency (A‐1 ATD, n = 2), progressive familial intrahepatic cholestasis (PFIC, n = 2), cystic fibrosis (n = 1), primary biliary cirrhosis (PBC, n = 1), neonatal hepatitis (n = 1), embryonal sarcoma (n = 1), Caroli disease (n = 1), hepatocellular carcinoma (HCC, n = 1), and chronic rejection after liver transplantations for PSC (n = 1). All patients and grafts survived at median follow‐up of 6.4 years (range 1.2‐12.9 years). Median domino recipient age was 16.2 years (range 0.6‐64.6 years) and median MSUD recipient age was 17.6 years (range 4.8‐32.1 years). There were no vascular complications during the early postoperative period, one patient had portal vein thrombosis 3 years after DLT and a meso‐Rex bypass was successfully performed. Small for size syndrome (SFSS) occurred in reduced left lobe DLT recipient and was managed successfully with conservative management. Biliary stricture developed in 2 patients and was resolved by stenting. Comparison between DLT and MSUD recipients' peak postoperative ALT results and PELD/MELD scores showed lower levels in DLT group ( P ‐value <.05). Conclusions: Patient and graft survival in DLT from MSUD donors was excellent at short‐ and long‐term follow‐up. Metabolic functions have been normal in all recipients on a normal unrestricted protein diet. Ischemia preservation injury based on peak ALT was significantly decreased in DLT recipients. Domino transplantation from pediatric and adult recipients with selected metabolic diseases should be increasingly considered as an excellent option and alternative to deceased donor transplantation, thereby expanding the living donor pool. This, to date, is the largest world experience in DLT utilizing livers from patients with MSUD.